Protein synthesis early in the developmental cycle of Chlamydia psittaci. - Plaunt, M R (1988)
The incorporation of [35S]methionine into protein by intracellular and host-free Chlamydia psittaci 6BC was analyzed at intervals between 15 min and 28 h postinfection by autoradiography of sodium dodecyl sulfate-polyacrylamide gels. The profiles of proteins synthesized in the two systems were similar at all times, indicating that the host-free system can be used to monitor the temporal expression of genes in chlamydiae. The host-free system permitted detection of synthesis of chlamydial proteins as early as 15 min postinfection. Some of the proteins synthesized during the initial phases of reorganization of elementary bodies to reticulate bodies either were not synthesized or were synthesized in greatly reduced amounts during the other phases of the developmental cycle. The effects of rifampin and actinomycin D indicated that host-free protein synthesis was at least partially dependent on the initiation and continuation of RNA synthesis in the isolated organisms.